Creative resources for the early childhood classroom - Herr, Judy. 4 0 16; Libby-Larson, Yvonne; 5 (Australia ;;Clifton Park, NY : Thomson Delmar Learning, 2009)
A theme-based curriculum planner with seventy different themes containing a variation of content including bulletin board ideas, parent letters, music and games, arts and crafts, fingerplay, and dramatic play covering a variety of subject areas; and includes a CD-ROM with assessments, lesson plan forms, and evaluations.
Includes bibliographical references (p. 715-718) and indexes.
Professional;Professional
System requirements for computer disc: Pentium; WIN 2000/XP/2003; CD-ROM drive; Adobe Acrobat Reader.;System requirements for computer disc: PowerPC/100MHz; OS 9.0/X; CD-ROM drive; Adobe Acrobat Reader.
Keywords: 2 -- 0; 6; Curricula.;Curricula. -- Education, Preschool;Unit method of teaching.;Preschool education; 20; 2